2016
DOI: 10.3390/nu8010040
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Whole-Grain Bread and Risk of Colorectal Cancer among Norwegian Women (the NOWAC Study)

Abstract: There is evidence that consumption of foods containing dietary fiber decreases the risk of colorectal cancer (CRC). Whole grains contain dietary fiber, as well as a range of micronutrients and bioactive compounds, but the association between the consumption of whole grains and the risk of CRC remains less studied. The aim of the present study was to investigate the association between whole-grain bread consumption and CRC incidence among Norwegian women, using data from a prospective cohort study (the Norwegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Whole grains are an important source of dietary fiber, and in contrary to refined grains, whole grains are rich in a variety of micronutrients and bioactive substances, including vitamins, minerals, antioxidants, phytoestrogens and other phytochemicals . So far, only eight prospective studies have examined the association of whole grains with risk of CRC and three studies reported a beneficial association …”
Section: Introductionmentioning
confidence: 99%
“…Whole grains are an important source of dietary fiber, and in contrary to refined grains, whole grains are rich in a variety of micronutrients and bioactive substances, including vitamins, minerals, antioxidants, phytoestrogens and other phytochemicals . So far, only eight prospective studies have examined the association of whole grains with risk of CRC and three studies reported a beneficial association …”
Section: Introductionmentioning
confidence: 99%
“…WGs are an important source of DF, and, in contrast to refined grains, contain a range of bioactive phytochemicals . WGs can, therefore, provide protective action against chronic diseases beyond providing fiber and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…However, whole grains contain fibers, as well as a range of micronutrients and bioactive compounds, ref. [56] and whole grain wheat consumption may enhance antioxidant defense systems and reduce the risk of cancer [57].…”
Section: Discussionmentioning
confidence: 99%
“…Rhodium (Rh), at 200 ng/mL was used as internal standard. Data were acquired for 80 Se, 56 Fe, 66 Zn, 65 Cu.…”
Section: Metal Trace Element Determination In Plasma Samplesmentioning
confidence: 99%